ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI TEMA 7 SUBTEMA 1 PERKEMBANGAN TEKNOLOGI PRODUKSI PANGAN KELAS III DI SEKOLAH DASAR 105332 SEI BLUMAI TANJUNG MORAWA - Milda Verawati Ndraha; Putri juwita (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the application of the Problem Based Learning learning model used by teachers on the material theme 7 sub-themes 1 on the development of food production technology for class III in elementary school 105332 Sei Blumai Tanjung Torawa. The location of this research was carried out at SD Negeri 105332 Sei Blumai Tanjung Morawa. The method used is descriptive qualitative method. The instruments used in this study were observation and interviews. Data collection techniques in this study used observation sheets, interviews and documentation. The participants selected by the researcher were class III teachers and 19 students. The results of this study indicate that the teacher only carries out 4 of the 5 phases according to the syntax of the problem-based learning model. The application of the Problem Based Learning learning model to the subject matter of the development of food production technology which was carried out in class III SD Negeri 105332 Sei Blumai seems to have been carried out well. Student response to learning using problem based learning is said to be positive and it can be concluded that learning using the Problem Based Learning model has been able to be followed by students. The application of the problem-based learning learning model to class III students at SD Negeri 105332 is classified as good and successful when viewed from fulfilling the criteria for the implementation of the learning steps and also the scores produced by the teacher during the learning process